DEVELOPMENT OF A FOOD FREQUENCY QUESTIONNAIRE FOR QUILOMBOLA POPULATIONS IN RIO GRANDE DO SUL STATE, BRAZIL - Mariana Espinoza Rivas; Pauline Müller Pacheco; Fernanda Souza de Bairros; Marilda Borges Neutzling (Universidade do Estado do Rio de Janeiro, 2016)
AIM: To develop a food frequency questionnaire (FFQ) to investigate dietary intake of adults in the maroon communities in  Rio Grande do Sul. Methods: The FFQ was based on prior administration of 24-hour recalls (24hRs) used in  a cross-sectional study conducted in 2011 with a representative sample of   maroon communities in  Rio Grande do Sul (RS). 589 dietary recalls were collected, generating a list of 163 food items. To construct the food list of the FFQ, we selected the items that had a frequency of occurrence of at least 5%.and those that showed a percentage contribution to the intake of energy and nutrients of interest in the study. Results: The most frequently consumed foods by the quilombola population were rice, soybean oil, coffee, beans, breads, sugar and red meat. The food with the highest contribution to calorie intake was  homemade bread, as well as carbohydrates and sodium. The item that contributed  most to the intake of protein was red meat. For lipids, the major contributor was soybean oil. For fibers, the largest contributor was  beans, as well as potassium. The orange was the food that contributed most to the intake of vitamin C. The final list of the food frequency questionnaire consists of 65 food items. Conclusion: This study is an  important contribution to the identification ofeating habits of the maroon communities in  Rio Grande do Sul, due to the paucity of data on the subject. DOI: 10.12957/demetra.2016.23266